Discrete color centers in two-dimensional hexagonal boron nitride induced by fast neutron irradiation. Issue 39 (23rd September 2019) - Zhang, Hui; Lan, Mu; Tang, Ge; Chen, Feiliang; Shu, Zhiwen; Chen, Fengxiang; Li, Mo
Abstract : Fast neutron irradiation can induce discrete color centers in 2D hBN, without obvious aggregation at multilayer edges or grain boundaries. Abstract : Color centers in two-dimensional hexagonal boron nitride, as promising room-temperature quantum emitters, have attracted much research interest. Many methods have been performed to create color centers on hBN, but the induced color centers tend to aggregate at flake edges or grain boundaries. In this paper, fast neutron irradiation was implemented to generate color centers with a homogeneous and discrete distribution on 2D hBN multilayers. The density of induced color centers positively correlated with the neutron dose, and within an appropriate neutron dose range, the spectral uniformity of the induced color centers could be maintained well. In addition, first-principle calculations were performed to explore the atomic origin of the observed color centers, and the VB3N1 defect was in good agreement with our experimental results.